2015
DOI: 10.1007/s10508-015-0654-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral vs. Vaginal Sex Experiences and Consequences Among First-Year College Students

Abstract: To fully understand late adolescents’ experiences of oral sex, we must consider both risk and normative developmental perspectives. Sexual experiences include a range of behaviors, but research on sexual behaviors and consequences focuses primarily on vaginal sex. Oral sex occurs at rates similar to vaginal sex, and carries some, though less, risk than vaginal sex. The current study examined the event-level prevalence and consequences of oral sex compared to vaginal sex with other-sex partners in first year co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 56 publications
(98 reference statements)
0
26
0
Order By: Relevance
“…In the same report, more girls were reported to give oral sex than boys. Some researchers argued that gender differences in the reporting of sexual activity might be influenced by the perception of sexual pleasure, health risks and beliefs [156, 157]. A qualitative study further showed that men preferred to receive oral sex from their partners than to give their partners because they perceived receiving oral sex to be less risky and giving oral sex to be a dirty and dangerous practice [158].…”
Section: Discussionmentioning
confidence: 99%
“…In the same report, more girls were reported to give oral sex than boys. Some researchers argued that gender differences in the reporting of sexual activity might be influenced by the perception of sexual pleasure, health risks and beliefs [156, 157]. A qualitative study further showed that men preferred to receive oral sex from their partners than to give their partners because they perceived receiving oral sex to be less risky and giving oral sex to be a dirty and dangerous practice [158].…”
Section: Discussionmentioning
confidence: 99%
“…For example, young adults may experience anal sex and performing oral sex as less positive than vaginal sex (Lefkowitz et al, 2016; Malacad & Hess, 2010; Vasilenko, Maas, Lefkowitz, & Maggs, 2014). In contrast, young adults may perceive kissing or touching as less negative than vaginal sex, at least among women (Vasilenko et al, 2014).…”
Section: Emotional Consequences Of Sexual Behaviorsmentioning
confidence: 99%
“…Some of this research suggests that women may react more negatively to sexual behaviors than men (Bradshaw, Kahn, & Seville, 2010; Meier, 2007; Vasilenko, Lefkowitz, & Maggs, 2012). Additional research suggests that the type of sexual behavior performed may influence gender differences in emotional consequences; for example, women may feel more positively about vaginal sex than oral sex, whereas men find both behaviors similarly rewarding (Lefkowitz et al, 2016). These findings demonstrate the need to account for gender in understanding between-person differences in the consequences of sexual behaviors.…”
Section: The Role Of Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to man, woman has better sexual self-control therefore woman needs to deliberate before engaging in premarital sexual behavior. For example, woman considers the possibility of pregnancy and regret caused by premarital sexual behavior (Lefkowitz, Vasilenko, & Leavitt, 2016).…”
Section: Discussionmentioning
confidence: 99%